The Effect of the Glucosinolate Sinigrin on Alterations in Molecular Biomarkers of the Myocardium in Swiss Mice - Nikola Ferara; Vedran Balta; Domagoj Đikić; Dyana Odeh; Ana Mojsović-Ćuić; Lana Feher Turković; Dario Dilber; Anđelo Beletić; Irena Landeka Jurčević; Ivana Šola (Foods)
Glucosinolates are chemically stable compounds that exhibit biological activity in the body following hydrolysis catalyzed by the enzyme myrosinase. While existing in vitro and in vivo studies suggest that the hydrolysis products of glucosinolates predominantly exert beneficial effects in both human and animal organisms, some studies have found that the excessive consumption of glucosinolates may lead to toxic and anti-nutritional effects. Given that glucosinolates are primarily ingested in the human diet through dietary supplements and commercially available cruciferous vegetables, we investigated the in vivo effects of the glucosinolate sinigrin on molecular markers in the myocardia of healthy Swiss mice. This study aims to elucidate whether sinigrin induces positive or negative physiological effects in mammals following consumption. The alterations in myocardial parameters were assessed by measuring metabolic, inflammatory, structural, and antioxidant markers. Our findings revealed that subchronic exposure to sinigrin in the myocardia of female mice resulted in a significant increase (p ≤ 0.05) in the levels of the myokine irisin, matrix metalloproteinases (MMP-2, MMP-9), catalase (CAT), and total glutathione (tGSH), alongside a marked decrease (p ≤ 0.05) in the levels of atrial natriuretic peptide (ANP), compared to the control group consisting of both female and male mice. These results suggest that the hydrolysis products of sinigrin may exert a potentially toxic effect on the myocardial tissue of female mice and possess the capability to modulate transcription factors in vivo in a sex-dependent manner. This observation calls for further investigation into the mechanisms regulating the actions of glucosinolate hydrolysis products, their interactions with sex hormones, and the determination of permissible intake levels associated with both beneficial and adverse outcomes.